Bridging the Gap: English Language Needs Analysis for Informatics Engineering Students in Higher Education - Rika Bella Amanda Putri; Noor Aida Aflahah; Miftah Al Farhan; Hafizhatu Nadia (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
Needs analysis involves identifying and understanding learners’ necessities, lacks, and wants within a specific context. This study aimed to analyse these aspects among informatics engineering students in learning English. Using a qualitative interview approach, the research was conducted at a private university in Banjarmasin with one English lecturer and three informatics students as research participants. The limited number of participants was intentionally selected to allow for in-depth exploration of perspectives and experiences, which is consistent with the exploratory nature of qualitative needs analysis in ESP contexts. The findings revealed that students’ necessities are linked to academic and professional needs, particularly speaking skills and advanced English proficiency for effective communication. Their lacks included unbalanced teaching of the four language skills, limited evaluation, and varying proficiency levels. The students’ wants showed strong motivation for independent learning through songs, films, and social media, as well as a preference for more engaging and interactive classroom activities. These findings provide important implications for ESP curriculum development by emphasising the need for needs-based syllabus design, balanced skill integration, and the incorporation of discipline-relevant and technology-supported learning activities.